How great companies achieve great results with ordinary people - Sutton, Karen; Positeri, Jon; O'Reilly, Charles A.; Stanford Alumni Association (Carlifornia : Stanford Alumni Association, 2001)
Charles O'Reilly challenges the prevailing wisdom that companies must chase and acquire top talent in order to remain successful. He argues instead that the source of sustained competitive advantage already exixts within every organization
Title from title screen
Executive producer, Catherine O'Brien ; editor, Gordon Gurley
Lecturer, Professor Charles A. O'Reilly III
Keywords: Industrial management -- United States -- Case studies; Human capital -- United States -- Case studies